Moisture Conservation Under Mulches in the Eroded Terraced Soils of Ranchi - Choudhary, P.C.; Chatterjee, B.N. (Journal of Soil and Water Conservation, 2022)
The bay of Bengal branch of monsoon provides adequate rainfall from June to September to the Chotanagpur plateau; the differences between total rainfall receipts and the evaporation losses being always positive {Rahman & Satakopan 1934). But in subse-quent months from October onwards to May, the differences are always negative; the magnitudes are higher (225 to 325 mm) during dry spring and early summer months (March to May) than in the autumn and winter (63 to 116 mm.) months (October to December).